2016
DOI: 10.3791/53759
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Connectivity in the Primary Visual Pathway in Human Albinism Using Diffusion Tensor Imaging and Tractography

Abstract: In albinism, the number of ipsilaterally projecting retinal ganglion cells (RGCs) is significantly reduced. The retina and optic chiasm have been proposed as candidate sites for misrouting. Since a correlation between the number of lateral geniculate nucleus (LGN) relay neurons and LGN size has been shown, and based on previously reported reductions in LGN volumes in human albinism, we suggest that fiber projections from LGN to the primary visual cortex (V1) are also reduced. Studying structural differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…Depending on whether no or all partial volume voxels are accounted for as part of LGN volume, the measured volume of the LGN would be between 110.6 and 262.1 mm 3 (or ∼2.4-fold), thus making the partial volume uncertainty the major source of the variability in the LGN volume measurements. For example, the range of human LGN volume measured in proton density MR images of 100-240 mm 3 (Bürgel et al, 1999) or 112-276 mm 3 (Grigorian et al, 2016) is in good agreement with our estimate of the range of LGN volume of 110.6-262.1 mm 3 . The partial volume uncertainty can generally be decreased by increasing image resolution (McKetton et al, 2015;Aldusary et al, 2019), but that often results in lower CNR and, therefore, a much noisier image.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…Depending on whether no or all partial volume voxels are accounted for as part of LGN volume, the measured volume of the LGN would be between 110.6 and 262.1 mm 3 (or ∼2.4-fold), thus making the partial volume uncertainty the major source of the variability in the LGN volume measurements. For example, the range of human LGN volume measured in proton density MR images of 100-240 mm 3 (Bürgel et al, 1999) or 112-276 mm 3 (Grigorian et al, 2016) is in good agreement with our estimate of the range of LGN volume of 110.6-262.1 mm 3 . The partial volume uncertainty can generally be decreased by increasing image resolution (McKetton et al, 2015;Aldusary et al, 2019), but that often results in lower CNR and, therefore, a much noisier image.…”
Section: Introductionsupporting
confidence: 88%
“…The LGN volume measurements in our study were highly consistent between the raters, with the inter class correlation coefficients (ICCs) of 0.74 and 0.81, which are above the minimum value of ICC of 0.70 for reliable measurements (Cohen, 2001). As mentioned earlier, such high reproducibility rates among two raters for the LGN volume measurements from a low contrast and noisy 3D images, as part of routine imaging protocol, is comparable to images acquired on a 3T systems with multiple signal averaging of up to 30-40 using a proton density weighted sequence with a long acquisition time (Kelly et al, 2014;McKetton et al, 2014McKetton et al, , 2015Moro et al, 2015;Grigorian et al, 2016;Giraldo-Chica and Schneider, 2018;DeSimone and Schneider, 2019). However, the LGN volumes are hardly consistent between the previously reported studies (Table 4), ranging from 76 mm 3 (Li et al, 2012) to 267 mm 3 (Korsholm et al, 2007), with the average of the left and right LGN volumes of 149.6 ± 45.8 mm 3 (mean ± SD, n = 27).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…By quantifying the magnitude and principle direction of water diffusion within image voxels, DTI data can be used for reconstruction of principle white matter tracts, a technique referred to as tractography (Beaulieu, ). Grigorian et al used the technique to study the optic radiation and found that in albinism, fibres from lateral geniculate nucleus (LGN) to the primary visual cortex (V1) are reduced (Grigorian, McKetton, & Schneider, ).…”
Section: Introductionmentioning
confidence: 99%